Joe Celko's analytics and OLAP in SQL - Celko , Joe (Elsevier Science [distributor], 2006)
This book is not an in-depth look at particular subjects, but an overview of many subjects that will give the working RDBMS programmers a map of the terra incognita they will face—if they want to grow.